Ammonia volatilization from mixed mineral fertilizers containing urea - de Sousa Gurgel, Gabriela Cemirames; Ferrari, Anderson Claiton; Fontana, Ademir; Polidoro, José Carlos; de Andrade Martins Coelho, Leonardo; Zonta, Everaldo (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to select a method for estimating N-NH3 lost by volatilization and to determine these losses in mixed fertilizers containing urea. An experiment was conducted in a greenhouse in trays filled with sandy soil, with urea rates of 0, 50, 100, and 200 kg ha-1 N. Volatilized ammonia was quantified by three methods: CSA, semi-open collector; Sale, free and static semi-open collector; and CA, open collector. In a second experiment, volatilization of ammonia from 18 fertilizers mixed with urea, humic acids, and zeolite was evaluated in sandy and clayey soils, at 200 kg ha-1 N. CSA was the method with the highest N recovery, followed by Sale and CA. Sale is more suited for experiments with a high number of experimental units, since it is more practical. The mixed fertilizers with urea and humic acids (5 and 10%) and with urea and zeolite (10%) had the best results in the mitigation of ammonia volatilization, reducing N-NH3 losses in up to 38%. The treatments are more effective in mitigating volatilization losses in the sandy soil.